2010
DOI: 10.1021/es903179j
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Drivers of the Increasing Colored Organic Matter in Boreal Surface Waters

Abstract: Long-term monitoring of surface water quality has shown increasing concentrations of colored dissolved organic matter (CDOM) across large parts of the northern latitudes. This has increased purification costs for domestic water works. Appropriate abatement actions require better knowledge of the governing factors for the increase, and this has motivated a growing scientific interest in understanding the factors and mechanisms promoting the CDOM increase. A proposed water color model for an important raw water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 37 publications
6
66
0
Order By: Relevance
“…No significant trends in discharge could be identified, verifying results of Lischeid (2001a). Thus, in the catchment under study here, changes in hydrology as a cause for increased DOC concentrations, as proposed by other studies (Haaland et al, 2010;Köhler et al, 2008), are not very likely.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No significant trends in discharge could be identified, verifying results of Lischeid (2001a). Thus, in the catchment under study here, changes in hydrology as a cause for increased DOC concentrations, as proposed by other studies (Haaland et al, 2010;Köhler et al, 2008), are not very likely.…”
Section: Discussionsupporting
confidence: 85%
“…The aim of this study was to find support for the hypothesis that the long-term increase in DOC exports from catchments is not only due to a decline in sulfate or acid rain deposition or due to a decrease in ionic strength (Clark et al, 2010;Hruska et al, 2009), but also by changes in biogeochemical processes and DOC mobilisation processes and hydrological flow paths in the source areas (e.g., Haaland et al, 2010;Clark et al, 2012). Many studies have so far investigated DOC exports from catchments and the controls thereof (Clark et al, 2010), but fewer studies are available investigating the DOC source areas and the DOC in runoff in a complementary approach (Worrall et al, 2008;Clark et al, 2008Clark et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Signs of oscillations with 20, 11, 8-9, 3-5 and 2 years long periods can be observed, that generally corresponds to the results of earlier studies (Glazacheva, 1988;Klavins et al, 2002a). Increase of water color, known also as brownification, was frequently reported in many lakes and rivers of the Northern hemisphere (Driscoll et al, 2003;Frey and Smith, 2005;Monteith et al, 2007;Erlandsson et al, 2008;Haaland et al, 2010), including Latvian rivers as well (Klavins et al, 2012). Our data show that despite low data quality and short period of observations , statistically significant upward trends of color values can be found in both rivers (Table 3).…”
Section: Resultssupporting
confidence: 89%
“…However, over-reliance on simple models and purely statistical criteria may lead to overly simplistic views of the environment. If nothing else, it can be argued that more than 30 years of research into surface water DOC, and its links to acidification, acidity, climate and hydrology (Krug and Frink 1983;Laudon et al 1999;Erlandsson et al 2008Erlandsson et al , 2010Lepistö et al 2008;Clark et al 2010;Haaland et al 2010;Haei et al 2010;Löfgren et al 2010b;Löfgren and Zetterberg 2011), has shown that numerous factors influence or covary with surface water DOC. So, we must conclude that, on the basis of our current understanding, reality is over-determined but that models can be a useful tool for environmental hypothesis testing and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in [DOC] in surface waters may have important consequences for drinking water in Fennoscandia (Haaland et al 2010). The costs of water treatment for human consumption and the production of potentially carcinogenic trihalomethane compounds are correlated with [DOC] (Christman et al 1983).…”
Section: Introductionmentioning
confidence: 99%